Healthy Parenting Skills Program toward First-Time Father’s Skills on Caring for Newborn Baby - Khasanah, Uswatun; Suratni, Suratni (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Purpose: This study is to examine the effects of skills training program named healthy parenting program on first time father skills. The skills are baby bath and umbilical cord care, baby blanket, burping and handling the baby, baby lullaby and replace baby clothes.Method: This is a quasi experiment study. Sampling technique is purposive sampling with 30 first time father with 0-28 days new born baby. Sample equally assigned into experimental and control groups. Subject in experimental group received healthy parenting skills program, while control group was given routine care only. The instrument is observation guideline. Wilcoxon and Man Whitney Test are used to analyze data.Result: Father’ skills in experimental group after receiving the program are statistically increased from before the program (bathing and umbilical cord care, baby blanket, baby burping, baby handling, baby lullaby, replace baby clothes).Conclusion: Father’ skills in experimental group after receiving the program are statistically increased over control group (bathing and umbilical cord care, baby blanket skill, baby burping, baby handling, baby lullaby, replace baby clothes). Suggestions are the educational efforts by health-care professionals could beneficially be directed toward fathers throughout prenatal and postpartum periods. Health center in Indonesia should initiate class program directed to father in part of program in reducing neonates and post partum mothers health problems.